Antimicrobial susceptibility testing of Corynebacterium pseudotuberculosis originated from Caprine caseous lymphadenitis (CLA) cases - Chew, Ying Yi (2017)
Caseous lymphadenitis (CLA) is a chronic bacterial infectious disease caused by a gram-positive bacteria named Corynebacterium pseudotuberculosis infecting animals especially small ruminant resulting in economic losses to a farm. Despite of contagious infection, the use of antibiotics in most cases do not eliminate the disease totally. The possibility of antibiotic resistance towards available antibiotics should be considered. Using antimicrobial susceptibility testing, this study was aimed to identify the susceptibility of the microorganism towards selected antibiotics. Laboratory strain of Corynebacterium pseudotuberculosis was used to test against 14 antibiotics available using disc diffusion method and zone of inhibition was measured to determine the susceptibility. The microorganism was also tested against 4 selected antibiotics available using broth microdilution method and minimal inhibitory concentration(MIC) and minimum bactericidal concentration (MBC) were determined. The microorganism showed susceptibility to amoxicillin with or without clavulanic acid,ampicillin, cephalexin, enrofloxacin, erythromycin, gentamicin, neomycin, oxytetracycline, penicillin G, sulfamethoxazole-trimethoprim and tetracycline but showed resistance to streptomycin and polymixinB. Minimal bactericidal concentration for neomycin, gentamycin, penicillin g and erythromycin are 1.875 μg,0.25 μg, 20 μg, and 20 μg respectively. Minimum inhibitory concentration for neomycin, gentamycin, penicillin g and erythromycin are 0.9375 μg, 0.125 μg, 10 μg and 10 μg, respectively. From the study, the microorganism is susceptible to most of the antibiotic groups including penicillin, cephalosporin, macrolides, tetracycline and aminoglycosides except streptomycin. The microorganism is resistant to cyclic peptide group of antibiotic (polymixin B) .